Los espacios productivos agustinos en la transformación del territorio de la jurisdicción eclesiástica de la orden de San Agustín en Valladolid 1550-1856 - Villagómez Nieto, Urinda (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
The control of the territory exercised by San Agustin's order in Michoacan's Bishopric owed principally to its household tasks; it was characterized as one of the religious orders that formed an important part in the process of conformation of the territory in the colonial period across the agrarian company that it constituted. The convent of Valladolid, for their strategic location and its political and administrative functions generated and propitiate the evangelizing mission of the order and also the agrarian company agustina in Michoacan's Bishopric. The territory of the ecclesiastic jurisdiction of the convent in Valladolid, achieved its maximum extension on having been founded and was diminishing in different moments during the colonial period; nevertheless, the same thing did not happen with the productive units acquired in the 16th century, but they managed to shape household tasks that were a part of the large estate of San Agustin's order in Michoacan. In the present study the transformations are analyzed in the extension of the territory of the ecclesiastic jurisdiction and the conformation of the household tasks that they acquired inside the jurisdiction of the convent in the moment of its maximum extension, which continued being administered by the convent of Valladolid during the whole colonial period, in spite of the fact that these were not already inside the ecclesiastic jurisdiction. This work has as general aim to elaborate the hypothetical reconstruction of the territorial structure of the ecclesiastic jurisdiction of the agustino ?s convent of Valladolid, focusing the analysis in the transformation of the territory in the period included from 1550 to 1856. We think that the productive spaces agustinos administered by the convent of Valladolid reverberated in the transformation of the territory across the appropriation of the natural resources of the zone, of the managing of the indigenous workforce and of the control on the production of the region, all these factors in a constant process of integration and conflict.

El control del territorio ejercido por la orden de San Agustín en el Obispado de Michoacán se debió principalmente a sus haciendas; se caracterizó como una de las órdenes religiosas que formó parte importante en el proceso de conformación del territorio en el periodo colonial a través de la empresa agraria que constituyó. El convento de Valladolid, por su ubicación estratégica y sus funciones político-administrativas generó y propicio la misión evangelizadora de la orden y también la empresa agraria agustina en el Obispado de Michoacán. El territorio de la jurisdicción eclesiástica del convento en Valladolid, logró su máxima extensión al fundarse y fue reduciéndose en diferentes momentos durante el periodo colonial; sin embargo, no sucedió lo mismo con las unidades productivas adquiridas en el siglo XVI, sino que lograron conformar haciendas que fueron parte del latifundio de la orden de San Agustín en Michoacán. En el presente estudio se analizan las transformaciones en la extensión del territorio de la jurisdicción eclesiástica y la conformación de las haciendas que adquirieron dentro de la jurisdicción del convento en el momento de su máxima extensión, las cuales continuaron siendo administradas por el convento de Valladolid durante todo el periodo colonial, a pesar de que estas no estaban ya dentro de la jurisdicción eclesiástica. En este trabajo se tiene como objetivo general elaborar la reconstrucción hipotética de la estructura territorial de la jurisdicción eclesiástica del convento agustino de Valladolid, enfocando el análisis en la transformación del territorio en el periodo que abarca de 1550 a 1856. Consideramos que los espacios productivos agustinos administrados por el convento de Valladolid repercutieron en la trasformación del territorio a través de la apropiación de los recursos naturales de la zona, del manejo de la fuerza de trabajo indígena y del control sobre la producción de la región, todos estos factores en un constante proceso de integración y conflicto.
Facultad de Arquitectura. Maestría en Arquitectura, Investigación y Restauración de Sitios y Monumentos
Keywords: info:eu-repo/classification/cti/4; FA-M-2006-0011; Espacios; Productivo; Obispado; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1545